2014
DOI: 10.3389/fnbeh.2014.00317
|View full text |Cite
|
Sign up to set email alerts
|

Reacquisition of cocaine conditioned place preference and its inhibition by previous social interaction preferentially affect D1-medium spiny neurons in the accumbens corridor

Abstract: We investigated if counterconditioning with dyadic (i.e., one-to-one) social interaction, a strong inhibitor of the subsequent reacquisition of cocaine conditioned place preference (CPP), differentially modulates the activity of the diverse brain regions oriented along a mediolateral corridor reaching from the interhemispheric sulcus to the anterior commissure, i.e., the nucleus of the vertical limb of the diagonal band, the medial septal nucleus, the major island of Calleja, the intermediate part of the later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 82 publications
(140 reference statements)
8
44
0
Order By: Relevance
“…The current work thus for the first time presents direct evidence of an alteration in network activity in this region that is associated with drug and natural reward conditioning. These electrophysiological findings are reminiscent of activation data obtained with IEG markers that indicate that conditioning to cocaine or dyadic social interaction does not only engage the nucleus accumbens proper but involves the neighboring regions as well [5]. …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The current work thus for the first time presents direct evidence of an alteration in network activity in this region that is associated with drug and natural reward conditioning. These electrophysiological findings are reminiscent of activation data obtained with IEG markers that indicate that conditioning to cocaine or dyadic social interaction does not only engage the nucleus accumbens proper but involves the neighboring regions as well [5]. …”
Section: Discussionmentioning
confidence: 83%
“…In rats, only 4 episodes of social interaction are sufficient to not only reverse place preference from cocaine to social interaction, but also to inhibit the cocaine-induced reexpression of cocaine-conditioned place preference (CPP) [4,5]. Furthermore, in a concurrent CPP paradigm, intraperitoneal injections of 15 mg/kg cocaine and social interaction compete as rewards of the same reward strength [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Another nonpharmacologic stimulus that may engender addictive behavior, internet gaming, is already on its way to be incorporated into mental disorder compendia, as evidenced by its inclusion as a “condition for further study” in the DSM5 [25]. To emphasize, any motivated behavior, including food seeking and consumption [27], carries the risk of becoming addictive, with the nucleus accumbens (see, e.g., [10,17,18,19,20,21,22,23]) and, possibly, the whole accumbens corridor [10,28,29] as the central neuroanatomic hot spot of the motivational neuronetwork (reward pathways) and dopamine as the major neurotransmitter driving motivated behavior. Interestingly, food and power share the paradox of being both essential for our survival as well as becoming extremely harmful for us if abused.…”
Section: Introductionmentioning
confidence: 99%
“…We chose the conditioned place preference (CPP) paradigm (Bardo et al, 1995 ; Zernig et al, 2007 ; Prast et al, 2014 ) for this purpose, as CPP allows to quantify, in a drug-free state, to what degree previously neutral contextual stimuli have acquired appetitive properties after having been paired with the drug on a minimal number of occasions, i.e., only 4 times (Fritz et al, 2011 ; Kummer et al, 2011 ; Prast et al, 2014 ). We had previously demonstrated in rats (Prast et al, 2014 ) that the time spent in the cocaine associated compartment was strongly correlated with the degree of activation, i.e., expression of the immediate early gene (IEG) Early Growth Related Protein 1 (EGR1), in the whole accumbens corridor, i.e., in a region stretching from the anterior commissure to the interhemispheric border and comprising the medial nucleus accumbens core (AcbCm) and shell (AcbShm), the major island of Calleja and lateral septum (ICjM + LSI), as well as the vertical limb of the diagonal band and medial septum (VDB + MS). Human functional imaging studies have confirmed the important role of the accumbens in drug addiction (Breiter et al, 1997 ; Breiter and Rosen, 1999 ; Haber and Rauch, 2010 ) and anxiety (Levita et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following the seminal paper by Everitt and coworkers (Lee et al, 2005 ), we decided to use the IEG EGR1 as a marker for neuronal activation in our paradigm (Fritz et al, 2011 ; El Rawas et al, 2012 ; Prast et al, 2012 , 2014 ). However, the most commonly used marker for neuronal activation in the accumbens is not EGR1, but another IEG, i.e., c-Fos (Hope et al, 1992 ; Singewald, 2007 ; Muigg et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%